S-glutathionylation, a redox switch disrupting angiogenic balance to promote the preeclampsia phenotype. (14th October 2021) - Lermant, A; Rabussier, G; Sneddon, C; Kerr, J; Lanz, H; Murdoch, C E
Abstract: Background: Elevation of circulating anti-angiogenic factors is pivotal in the development of the preeclampsia (PE) phenotype of incomplete vascular remodelling, hypertension and kidney dysfunction during pregnancy. Oxidative stress is explicitly linked to PE with high levels measurable in the placenta. Yet antioxidant therapy has failed, in some cases worsening pregnancy outcomes. The modulation of protein activity by reversible oxidative post-translational modifications (oxPTM) under low levels of reactive oxygen species is emerging as an important "redox-switch" mechanism in cardiovascular diseases, although oxPTM have not been investigated in the context of PE. Of significance, S-glutathionylation is a common oxPTM which reversal by glutaredoxin (Grx) is predominant in preeclamptic placenta and was associated with attenuated revascularisation and sFlt-1 elevation in mice. Purpose: We aimed to identify the molecular basis for how S-glutathionylation reversal by Grx may contribute to pregnancy-induced vascular complications by modulating angiogenic signalling at the maternofoetal interface. Methods: We combined physiological in vivo assessment with bioinformatics proteomic analysis and exon-level microarray to investigate the role of S-glutathionylation in the development of PE phenotype. In vitro studies using primary endothelial cells (EC) and iPS-derived trophoblasts investigated the effects of oxPTM reversal on angiogenic signalling in individual placental cell types and the functional consequences were assessed in 3D models replicating early-pregnancy events. Results: Overexpressing Grx transgenic mice (TG) developed gestational hypertension, kidney dysfunction and elevated plasma levels of the anti-angiogenic factor sFlt-1 compared to their littermate controls (WT) during timed pregnancy. Grx-mediated oxPTM reversal in EC disrupted angiogenic sprouting and promoted anti-angiogenic signals by increasing sFlt-1:PlGF ratio and decreasing endoglin levels. The rise in sFlt-1 was associated with an isoform switch promoting sFlt-e15a over sFlt-i13. In trophoblasts, Grx overexpression inhibited migration and syncytialisation and modulated angiogenic balance in a cell type-specific manner. The sFlt1-e15a:PlGF ratio was increased in syncytiotrophoblasts and decreased in extra-villous trophoblasts, while endoglin expression was decreased in both cell types. A genome-wide exon-level profiling of TG vs WT mice placenta revealed a global alteration of alternative splicing events. Conclusion: Grx-mediated removal of oxPTM directly disrupts placental angiogenic balance via dysregulation of sFlt-1 isoforms, which may promote the PE phenotype of impaired vascular remodelling, hypertension and kidney dysfunction during pregnancy. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): Horizon 2020 - Marie Skłodowska-Curie grant agreement (iPLACENTA)